Antibacterial Activity of the Ethanolic Extracts Derived from Leaves and Pseudobulbs of Some Orchids Belonging to Coelogyne Genus Against Enterobacter cloacae Strain - Buyun, Lyudmyla; Tkachenko, Halyna; Kurhaluk, Natalia; Gyrenko, Oleksandr; Kovalska, Lyudmyla; Góralczyk, Anna; Tomin, Vladimir; Osadowski, Zbigniew (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2019)
Our previous study reported that the selected orchids belonging to the genus Coelogyne exhibited fairly strong antioxidant and antimicrobial activities. This paper focused on the assessment of the antibacterial activity of eight plants, i.e. Coelogyne cristata Lindl., C. fimbriata Lindl., С. flaccida Lindl., C. huettneriana Rchb.f., C. ovalis Lindl., C. speciosa (Blume) Lindl., C. tomentosa Lindl. and C. viscosa Lindl. towards clinical cefuroxime-resistant Enterobacter cloacae strain. Antibacterial activity was evaluated qualitatively and quantitatively using disc diffusion assay. The ethanolic extracts obtained from leaves and pseudobulbs of five orchids belonging to the Coelogyne genus were found to exhibit fairly strong antibacterial activity towards Enterobacter cloacae strain used, the diameter of inhibition zones varied from 8-25.5 mm. It has been observed that ethanolic extract obtained from pseudobulbs of eight species from Coelogyne genus revealed the highest antibacterial activity (11-25.5 mm as the diameter of inhibition zone) as compared to ethanolic extracts obtained from leaves of the same Coelogyne species. These findings provide a clear demonstration of the generally overlooked importance of the collection of tropical plants accumulated at the Botanic Gardens, orchids collection, in particular, as an important source of new chemical substances with potential therapeutic effects, including antifungal activity.